Geopolymer concrete for ambient curing condition - Nath, Pradip; Sarker, Prabir (Engineers Australia, 2012)
Recent studies on the various properties of heat-cured geopolymer concrete have shown its suitability for applications such as precast concrete members. Development of geopolymer concrete suitable for curing at ambient temperature will widen its application to concrete structures. This study aimed to achieve fly ash-based geopolymer concretes suitable for ambient curing condition. Class F fly ash was used as the base material which was reacted by sodium hydroxide and sodium silicate solutions. Ground blast furnace slag was added in different proportions to the mix to enhance the early age properties of concrete. Setting times of geopolymer pastes, workability of fresh concrete and compressive strength after curing at 20-23ºC were investigated. Results were compared for the varying proportions of slag and alkaline activator in the mix. Inclusion of slag reduced the setting time to values comparable to that of ordinary Portland cement paste and improved the early-age compressive strength significantly. Setting time and compressive strength of geopolymers varied with the variation of alkaline activator to fly ash ratio and sodium silicate to sodium hydroxide ratio in the alkaline activator solution. Generally, fly ash and slag blend has improved the early-age mechanical properties of geopolymer concrete cured at ambient condition.